Feasibility of Tea/Tree Intercropping Plantations on Soil Ecological Service Function in China - Feng, Y.; Sunderland, T.C.H. (MDPI, 2023)
In order to explore whether tea/tree intercropping plantations have positive effects on soil ecosystem services functions, the possible effects of intercropping cultivation of 151 different tea and other species’ intercropping setups were summarized and analyzed in terms of three aspects of soil ecological service functions (supply services, support services, and regulating services). An ArcGIS map was plotted to show the distribution of existing intercropping plantations in China up to June 2021. Furthermore, it was concluded that the benefits of intercropping tea plantations exceeded those of monocropping tea plantations in terms of soil ecosystem service functions, such as water retention capacity, mineral contents, effects on energy transformation, and regulating environmental conditions. Intercropping tea plantations were more sustainable than regular tea plantations because of the different degrees of variability and benefits in all three aspects mentioned above. However, tea and tree intercropping plantations often require careful planning and preliminary experimentation to determine the type of intercropping that will have positive impacts, especially in the long term.